Presuppositions in Retno Marsudi’s Speech at the UN General Assembly in New York - Ruth Indriani Napitupulu (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
Assumption toward something that has happened early before an utterance is called presupposition. Studying presupposition helps people clarify a conversation. According to Yule’s theory, presupposition is categorized into six types, which are existential, factive, non-factive, lexical, structural, and counter-factual presuppositions. In this research, the writer attempts to identify and analyze presuppositions found Retno Marsudi’s Speech at the UN General Assembly in New York, on Thursday, 25th May 2021. Descriptive qualitative method is applied since the data is in the form of sentences. The result shows that there are four types of presupposition. Based on the analysis, there are 33 presuppositions, namely 18 existential presuppositions, 1 factive presupposition, 13 lexical presuppositions, and 1 structural presupposition.